Pemberdayaan Perempuan oleh Kelompok Perempuan (Dasawisma Sekar Melati) Kecamatan Imogiri Kabupaten Bantul - Meita Rahmawati (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
Women are always considered helpless especially in the economic field. Women need to be empowered so that they can break the assumption of the community that women are always underdeveloped. This research was conducted to find out about empowerment activities carried out by the Dasawisma group